Distribution of bioluminescent fungi across old-growth and secondary tropical rain forest in Costa Rica - Carolina Seas-Carvajal; Gerardo Avalos (Revista de Biología Tropical, 2013)
Most research on bioluminescent fungi is concentrated on their taxonomic relationships, while the basics of their natural history and ecological relationships are poorly understood. In this study, we compared the distribution of bioluminescent fungi between old-growth and secondary forest as related to four different soil types at the tropical rainforest of La Selva Biological Station in Costa Rica. The study was conducted during the wet season of 2009. Bioluminescent fungi were sought following eight different transects distributed evenly in old-growth and secondary forests across four different soil types, covering an area of 9 420m². We found fungi in four different substrates: litter, fallen branches, dead trunks, and roots, for a total of 61 samples. Correspondence analysis showed that the occurrence of fungi and soil types were related (inertia=0.21, p=0.071). We found a significant relationship between the presence of fungi and the distribution of soil types (X²=18.89, df=9, p=0.026). We found only three samples with fruiting bodies, two of which had Mycena and the other had one fungus of the order Xylariales (possibly Hypoxylon sp., Kretzschmariella sp., Xylaria sp.). Future work will concentrate on exploring other aspects of their ecology, such as their dispersal and substrate preference. This information will facilitate field identification and will foster more research on the distribution, seasonality, reproductive phenology and ecological requirements of this group of Fungi.